2017
DOI: 10.1128/iai.00422-17
|View full text |Cite
|
Sign up to set email alerts
|

17β-Estradiol Dysregulates Innate Immune Responses to Pseudomonas aeruginosa Respiratory Infection and Is Modulated by Estrogen Receptor Antagonism

Abstract: Females have a more severe clinical course than males in terms of several inflammatory lung conditions. Notably, females with cystic fibrosis (CF) suffer worse outcomes, particularly in the setting of infection. Sex hormones have been implicated in experimental and clinical studies; however, immune mechanisms responsible for this sex-based disparity are unknown and the specific sex hormone target for therapeutic manipulation has not been identified. The objective of this study was to assess mechanisms behind t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(42 citation statements)
references
References 52 publications
3
35
0
Order By: Relevance
“…Consistent with our observations, female mice intranasally infected with P. aeruginosa have increased rates of mortality and levels of inflammatory cytokines, in addition to increased neutrophil necrosis (15). We observed that depletion of neutrophils led to increased bacterial burdens in our study irrespective of sex, so the observed increase in neutrophil necrosis in females both in our study and Abid et al (15) is a likely reason behind the sex bias. Why this is not observed in other bacterial respiratory models in mice could be due to differences in animal models and humans.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Consistent with our observations, female mice intranasally infected with P. aeruginosa have increased rates of mortality and levels of inflammatory cytokines, in addition to increased neutrophil necrosis (15). We observed that depletion of neutrophils led to increased bacterial burdens in our study irrespective of sex, so the observed increase in neutrophil necrosis in females both in our study and Abid et al (15) is a likely reason behind the sex bias. Why this is not observed in other bacterial respiratory models in mice could be due to differences in animal models and humans.…”
Section: Discussionsupporting
confidence: 91%
“…Direct evidence as to how the hormones influence these conditions is not fully known. While our own respiratory studies with Staphylococcus aureus, Klebsiella pneumoniae, or Streptococcus pneumoniae (46)(47)(48)(49) have not indicated a significant susceptibility for any particular sex in mouse models, it has been shown that female mice are more susceptible to respiratory Pseudomonas aeruginosa infection (15). Consistent with our observations, female mice intranasally infected with P. aeruginosa have increased rates of mortality and levels of inflammatory cytokines, in addition to increased neutrophil necrosis (15).…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Our wide-ranging experiences of how these are dealt with around the world can identify areas to be addressed. The gender-gap in CF survival, a concept discussed frequently in the medical literature [1][2][3][4][5][6][7][8] , is considered visible in many of our regions, is incompletely understood and requires further research.…”
Section: Introductionmentioning
confidence: 99%